Further analysis of natural antibodies against ischemic stroke - Qi, Jingjing; Jiang, Quanhang; Wang, Peng; Wang, Zhenqi; Zhang, Xuan (Frontiers in Neurology, 2023)
Background Our previous study revealed that circulating levels of IgG natural antibodies (NAbs) for vascular endothelial growth factor receptor 1 (VEGFR1) were significantly decreased in patients with arteriosclerosis compared with control subjects. To enhance the sensitivity of an enzyme-linked immunosorbent assay (ELISA) developed in-house for antibody testing, the present work was designed to investigate additive signals in the in-house ELISA developed with the combination of two or more linear peptide antigens derived from target proteins of interest, including VEGFR1, oxidized low-density lipoprotein receptor 1 (LOX-1), interleukins 6 (IL6) and 8 (IL8). Methods A total of 218 patients with ischemic stroke and 198 healthy controls were enrolled and an in-house ELISA was developed with linear peptides derived from VEGFR1, LOX-1, IL6, and IL8 to detect their IgG levels in plasma. Results Compared with control subjects, plasma levels of IgG NAbs for the IL6-IL8 combination were significantly lower in female patients (Z = −3.149, P = 0.002), whereas male patients showed significantly lower levels of plasma anti-VEGFR IgG (Z = −3.895, P < 0.001) and anti-LOX1a IgG (Z = −4.329, P < 0.001). Because plasma levels of IgG NAbs for both the IL6-IL8-LOX1a-LOX1b combination and the VEGFR1a-VEGFR1b-LOX1a-LOX1b combination were significantly lower in the patient group than the control group, receiver operating characteristic (ROC) analysis was performed and the results showed that the VEGFR1a-VEGFR1b-LOX1a-LOX1b combination had an area under the ROC curve (AUC) of 0.70 for its IgG assay with a sensitivity of 27.1% against the specificity of 95.5% and that the IL6-IL8-LOX1a-LOX1b combination had an AUC of 0.67 for its IgG assay with a sensitivity of 21.1% against the specificity of 95.5%. Spearman correlation analysis showed that plasma IgG NAbs against the IL6-IL8 combination were positively correlated with carotid plaque size only in male patients (r = 0.270, p = 0.002). Conclusions Circulating IgG NAbs for the target molecules studied may be potential biomarkers for a subgroup of ischemic stroke and also contribute to the gender differences in clinical presentation of the disease.